Ahlussunnah Wal Jama’ah (ASWAJA) Sebagai Basis Nilai Dasar Pergerakan dan Pemikiran Pergerakan Mahasiswa Islam Indonesia (PMII) - Muharam, Suhari (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The Islamic Students Movement of Indonesia is an organization aimed at the formation of Indonesian Muslims who are afraid of Allah SWT, righteous, knowledgeable, competent, and responsible in practicing their knowledge and commitment to the realization of the ideals of Indonesia's independence. The purpose of this research is to know and analyze the values contained in the Ahlussunnah Wal Jama’ah (ASWAJA), which is made PMII, as the basis of the value of thought and the theological foundation. The method used in this research is the qualitative descriptive approach, which is a way to find new meanings, explain a condition of existence, determine the frequency of occurrence of something, and categorize information. In this study, there are four principles of values that can be transformed into the direction of the PMII movement, which is a framework of thinking to be able to formulate concrete solutions to the problems that exist in the current reality. There are four kinds of worshippers in the Qur’an: al-Tawassuth, Al-Tawazun, al-Asamuh, and al-I’tidal.